MENENTUKAN GRUP GALOIS PADA POLINOMIAL RASIONAL DENGAN PENGEMBANGAN METODE STAUDUHAR - Juli Loisiana Butar-butar (JURNAL CURERE, 2019)
After it was found the general solution of by radicals of polynomial up to degree four, appear a problem that there is no general solution by radicals of polynomial degree five. Galois theory had appeared as the answereof this problem and it has given a big role in development of mathematics in particular Algebra and Number Theory. To determine Galois group from a rational monic polynomial f(x) with integer coefficients of degree n is determining automorphism group from roots of f(x). Therefore, Galois Group f(x)is a subgroup of Sn. Method of Stauduhar as one manner to determining Galois Group f(x), that is finding the least maximal transitive subgroup that act on roots of f(x).In this paper will be studied method of Stauduhar using Dedekind’s Theorem.